Empower Finance Framework: Financial Decisions as Instruments of Empowerment and Sustainability - Murniati, Sitti; Herlina (SAFE-Network, 2025)
This paper develops the Empower Finance Framework, a conceptual model that positions financial decisions as instruments of empowerment and sustainability. The study aims to explain how financial choices shape individual capability, autonomy, adaptive behavior, and long term resilience. The research applies a structured qualitative analytical method consisting of conceptual analysis, model construction, analytical mapping, and interpretative evaluation. The framework integrates financial decision pathways, empowerment mechanisms, sustainability patterns, and contextual moderating factors. The results show that financial decisions operate through cyclical processes that generate capability enhancement, strengthen decision autonomy, and reinforce adaptive financial strategies. These mechanisms accumulate over time, producing sustainability outcomes such as financial stability, responsible behavior, and community level resilience. The discussion highlights that sustainable outcomes emerge not only from financial access but from empowered behavioral processes supported by conducive contextual conditions. The study concludes that the framework offers a comprehensive analytical tool for designing financial education programs, empowerment interventions, and policy initiatives aimed at improving financial well being. Recommendations for future research include empirical testing of the model and the exploration of contextual variations across different populations.